중국 대형할인점의 마케팅 믹스요인과 소비자 만족도에 대한 실증분석 - 박상수; 서운석 (중국연구, 37(0), 2006)
The purpose of this study is providing positive relevance between recognition of 6P's importance and consumer satisfaction in using foreign wholesale-warehouse. 6P includes Product, People, Presentation, Promotion, Place and Price. And also, this study makes it clear that the difference of each collective group between demographical characteristic and recognition of desire. Since, Chinese market is not a single market but a collective market by each separate market. To this purpose, this study using data of foreign wholesale-warehouse by making up a questionnaire to consumers who lives in Beijing, Shanghai and Tianjin. Throughout analysis, it verifies relevance between purchase satisfaction and Presentation and Price factors. And also, there are some differences in collective group. KCI Citation Count: 5